LOCAL WISDOM-BASED SOCIAL SCIENCE LEARNING - Agung S, Leo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The objective of Social Science learning in Junior High School (SMP/MTs) is tomake the students the good citizens. For that reason, Social Science learning isnot only the transfer of knowledge but also the transfer of values. Thus, theassessment of learning should pertain to cognitive, affective and psychomotoraspects. To achieve the goal, the learning model should be contextual orContextual Teaching and Learning (CTL), meaning that learning material shouldbe related to surrounding environment. For Surakarta City, surroundingenvironment becoming local wisdom and source of Social Science learning isBengawan Solo. For Social Science learning, Bengawan Solo can be studiedfrom Historical, Geographical, Economic and Sociological aspects. MakingBengawan Solo the learning source, the students of SMP/MTs in Surakarta Cityare expected to love more their environment, the local wisdom that can be amedium of reinforcing the character in dealing with globalization age.Keywords: Social Science Learning, CTL, Bengawan Solo, and Local Wisdom